A Feasibility Study in Application of a Gamma Scattering Technique for Inspecting Density Variation - Khiem, Le Hong; Trong, Tran Dinh; Thao, Nguyen Van (Communications in Physics, 2012)
Back-scattering gamma-rays have been extensively used for years as a nondestructive tool for inspecting the materials in different fields of the economy. The intensities of Compton scattering gamma-rays from the scattering medium strongly depend on its electron density and therefore in its mass density. This feature is very useful for using it as a viable tool for inspecting material. This work aims to investigate the feasibility of application of gamma scattering technique for inspecting density variation in some construction objects by Monte-Carlo simulation method. The gamma-ray sources of different energies and strengths have been used to extract the information of density variation for interior of sample by recording the backscattering gamma-rays with a gamma-ray detector. The results of our simulations confirm that the resolution for density variation in the inspected objects is quite good. The results should also prove useful in the optimum design of the nondestructive density gauges.